THE APPLICATION OF OLIVINE GEOTHERMOMETRY TO INFER CRYSTALLIZATION TEMPERATURES OF PARENTAL LIQUIDS: IMPLICATIONS FOR THE TEMPERATURE OF MORB MAGMAS - Falloon T.J.; Danyushevsky L.V.; Ariskin A.; Green D.H.; Ford C.E. (My University, 2007)
We have performed a detailed evaluation of three olivine geothermometers for anhydrous systems representing three different approaches to modelling olivine-melt equilibrium. The Ford et al. [Ford, C. E., Russell, D. G., Craven, J.A., Fisk, M. R., 1983. Olivine-liquid equilibria: Temperature, pressure and composition dependence of the crystal/liquid cation partition coefficients for Mg, Fe2+, Ca and Mn. J. Petrol., 24, 256-265.] geothermometer describes olivine liquidus temperature as a function of melt composition and pressure, and the composition of the liquidus olivine as a function of melt composition, pressure and temperature. The Herzberg and O'Hara [Herzberg, C., O'Hara, M.J., 2002. Plume-associated ultramafic magmas of Phanerozoic Age. Journal of Petrology, 43, 1857-1883.] geothermometer describes olivine liquidus temperature similarly to Ford et al. [Ford, C. E., Russell, D. G., Craven, J.A., Fisk, M. R., 1983. Olivine-liquid equilibria: Temperature, pressure and composition dependence of the crystal/liquid cation partition coefficients for Mg, Fe2+, Ca and Mn. J. Petrol., 24, 256-265.], and olivine composition as function of melt composition only. The Putirka [Putirka, K.D., 2005. Mantle potential temperatures at Hawaii, Iceland, and the mid-ocean ridge system, as inferred from olivine phenocrysts: evidence for thermally driven mantle plumes, Geochem. Geophys. Geosyst., 6, Q05L08, doi:10.1029/2005GC000915.] geothermometer describes both olivine liquidus temperature and composition as function of melt composition only. A comparison of these three geothermometers with experimental data at 0.1 MPa and 1.5 GPa reveals that the Ford et al. [Ford, C. E., Russell, D. G., Craven, J.A., Fisk, M. R., 1983. Olivine-liquid equilibria: Temperature, pressure and composition dependence of the crystal/liquid cation partition coefficients for Mg, Fe2+, Ca and Mn. J. Petrol., 24, 256-265.] geothermometer is the most successful in reproducing experimental temperatures and olivine-melt KD's. We therefore recommend that the Ford et al. [Ford, C. E., Russell, D. G., Craven, J.A., Fisk, M. R., 1983. Olivine-liquid equilibria: Temperature, pressure and composition dependence of the crystal/liquid cation partition coefficients for Mg, Fe2+, Ca and Mn. J. Petrol., 24, 256-265.] olivine geothermometer be used in parental liquid calculations that involve the incremental addition of olivine to obtain equilibrium with a target olivine phenocryst composition at low pressure. The thermometer of Putirka [Putirka, K.D., 2005. Mantle potential temperatures at Hawaii, Iceland, and the mid-ocean ridge system, as inferred from olivine phenocrysts: evidence for thermally driven mantle plumes, Geochem. Geophys. Geosyst., 6, Q05L08, doi:10.1029/2005GC000915.] was found to systematically calculate anomalously high temperatures for high MgO experimental compositions at both 0.1 MPa and 1.5 GPa. The application of the Ford et al. [Ford, C. E., Russell, D. G., Craven, J.A., Fisk, M. R., 1983. Olivine-liquid equilibria: Temperature, pressure and composition dependence of the crystal/liquid cation partition coefficients for Mg, Fe2+, Ca and Mn. J. Petrol., 24, 256-265.] geothermometer to calculate the temperatures of crystallization for parental MORB liquids in mid-crustal magma chambers reveals that there is an ~ 115 °C temperature range. The hottest MORB parental liquids have crystallisation temperatures of ~ 1345 °C (MgO contents ~ 16 wt.%) for a mid-crustal pressure of 0.2 Gpa. © 2007 Elsevier B.V. All rights reserved.
Keywords: GEOTHERMOMETERS; HAWAII; MANTLE PLUMES; MORB; OLIVINE; TEMPERATURE